Analysis of Local Culture of Sea Alms Ceremony in Cilacap Regency in the View of Islamic Law - Meli Aji Syah Putra (UM Purwokerto Press, 2023)
Islam, is one of the plurality of religions that has a definite law that comes from Allah SWT or known as Islamic law. Talking about Islamic Law which is a rule held by God for his people who are brought by a Prophet Muhammad SAW, both laws related to beliefs and laws related to actions carried out by all Muslims. The sea alms ceremony is one of the heritages in the form of ceremonial activities that not everyone carries out, but only certain people who have an interest in it. In the southern sea area, the Sea Alms Ceremony in Cilacap is also carried out by giving various offerings to the one who controls the southern sea known as Nyi Roro Kidul. The purpose of this research is to find out and analyze the local culture of the Sea Alms Ceremony in Cilacap Regency according to the views of Islamic Law and to find out the factors that hinder the practice of Islamic Law in the implementation of the Local Culture of the Sea Alms Ceremony in Cilacap Regency. This research on the Analysis of the Local Culture of the Sea Alms Ceremony in Cilacap Regency is a normative juridical research because this research must find data from studying document studies, namely using various secondary data such as laws and regulations, court decisions, and Islamic legal theory.